Islamic Financing Mechanisms for Renewable Energy Projects: Mapping Research Trends and Future Directions - Almustafa, Esmat (International Journal of Energy Economics and Policy, 2025)
This paper discusses the emergent trends in Islamic financing mechanisms for renewable energy projects, highlights their role in promoting economic growth, and discusses sustainability. By applying bibliometric analysis, cluster analysis (VOSviewer), and co-citation analysis, this study explores literature between 2008 and 2024 on the impact of Islamic finance on renewable energy projects. Data is collected from two major databases; Scopus and Web of Science Core Collection; key trends; influential publications; and future research directions. Findings show that Islamic financing mechanisms; including green sukuk and impact investing; are essential in supporting renewable energy investments. The study identifies key contributors such as Saudi Arabia; Malaysia; UAE; and Malaysia; with research focusing on the relationship between Islamic finance; ESG performance; renewable energy; and climate change mitigation. Future research may explore the integration of digital technologies; green innovation; and technological advancements in Islamic financing for renewable energy projects. The limitations include the reliance on Scopus and Web of Science databases, with further suggestions for incorporating additional databases and expanding keyword searches. This paper contributes to a better understanding of the intersection between Islamic finance and renewable energy, hence providing a good foundation for further research and practical applications in the field.